Roughening copper foil, copper foil with carrier, copper clad laminate and printed circuit board
By controlling the difference in the interface expansion area ratio and the level of the center part on the roughening surface of the copper foil, the problem of difficulty in taking into account the etchability and shear strength of the copper foil is solved, and the excellent etchability and high shear resistance of the printed circuit board are achieved. Strength improves circuit adhesion and yield.
Patent Information
- Application Number
- CN202180012213.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-02-04
- Filing Date
- 2021-01-20
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2041-01-20
AI Technical Summary
During the manufacturing process of printed circuit boards, it is difficult to take into account both the etchability and shear strength of the copper foil, resulting in easy peeling of the circuit and lowering the yield.
By controlling the interface expansion area of Sdr and the horizontal difference between the central part of Sk on the roughening surface of the copper foil, the interface expansion area ratio is set to be 3.50% or more and 12.00% or less at the cut-off wavelength of 0.55μm and 10μm, respectively. The horizontal difference of the portion is 0.15 μm or more and 0.35 μm or less, so that excellent etching properties and high shear strength are achieved.
In the manufacturing of copper clad laminated plate and printed circuit board, excellent etching properties and high shear strength are taken into account, and circuit adhesion and yield are improved.
Smart Images

Figure BDA0003775886210000211 
Figure HDA0003775886220000011 
Figure HDA0003775886220000021
Abstract
Description
Technical Field
[0001] The invention relates to a roughened copper foil, a copper foil with a carrier, a copper-clad laminate and a printed circuit board. Background Art
[0002] In recent years, the MSAP (modified semi-additive process) method has been widely used as a manufacturing method for printed circuit boards suitable for miniaturization of circuits. The MSAP method is a method suitable for forming extremely fine circuits. In order to utilize its characteristics, copper foil with a carrier is used. For example, Figure 1 and 2 As shown, the ultra-thin copper foil 10 is pressed onto the insulating resin substrate 11 using the prepreg 12 and the primer layer 13 to make it close, and the insulating resin substrate 11 has a lower circuit 11b on the base substrate 11a (step (a)); after the carrier (not shown) is peeled off, the via hole 14 is formed by laser perforation as needed (step (b)). Next, after chemical copper plating 15 (step (c)), masking is performed in a predetermined pattern by exposure and development using a dry film 16 (step (d)), and electroplating copper 17 is performed (step (e)). After the dry film 16 is removed to form the wiring part 17a (step (f)), the unnecessary ultra-thin copper foil between the adjacent wiring parts 17a and 17a is removed from their entire thickness by etching (step (g)), and the wiring 18 formed in a predetermined pattern is obtained. Here, in order to improve the physical adhesion between the circuit and the substrate, the surface of the ultra-thin copper foil 10 is usually roughened.
[0003] As a copper foil subjected to such a roughening treatment, for example, Patent Document 1 (Japanese Patent No. 6462961) discloses a surface-treated copper foil in which a roughening treatment layer, a rust-proof treatment layer, and a silane coupling layer are sequentially laminated on at least one side of the copper foil. Patent Document 1 also discloses that, for the purpose of manufacturing a printed circuit board having low transmission loss and excellent reflow heat resistance, the surface-treated copper foil has an interface expansion area ratio Sdr of 8% or more and 140% or less measured from the surface of the silane coupling layer, a root mean square slope Sdq of 25° or more and 70° or less, and a surface aspect ratio Str of 0.25 or more and 0.79 or less.
[0004] In fact, some copper foils with carriers that are excellent in fine circuit formation based on the MSAP method and the like have been proposed. For example, Patent Document 2 (International Publication No. 2016 / 117587) describes a copper foil with a carrier, which has an average distance between surface peaks on the peeling layer side of less than 20 μm and an extremely thin copper foil with a maximum height difference of the corrugation on the surface opposite to the peeling layer of less than 1.0 μm. According to the method, fine circuit formation and laser processing properties can be taken into account. In addition, Patent Document 3 (Japanese Patent Publication No. 2018-26590) discloses a copper foil with a carrier for the purpose of improving fine circuit formation, wherein the ratio of the maximum peak height Sp of the side surface of the ultra-thin copper layer according to ISO25178 to the height of the protruding peak Spk Spk is greater than 3.271 and less than 10.739.
[0005] Prior art literature
[0006] Patent Literature
[0007] Patent Document 1: Japanese Patent No. 6462961
[0008] Patent Document 2: International Publication No. 2016 / 117587
[0009] Patent Document 3: Japanese Patent Application Publication No. 2018-26590 Summary of the invention
[0010] In recent years, in order to form finer circuits through the above-mentioned MSAP method, the copper foil is required to be further smoothed and the roughening particles are miniaturized. However, the etching property of the copper foil related to the miniaturization of the circuit is improved by the smoothing of the copper foil and the miniaturization of the roughening particles, but the physical adhesion between the copper foil and the substrate resin is reduced. In particular, as the circuit becomes thinner, the physical stress (i.e., shear stress) applied to the circuit from the lateral direction during the installation process of the printed circuit board will cause the circuit to peel off easily, and the problem of reduced yield is obvious. In this regard, one of the physical adhesion indicators between the circuit and the substrate is shear strength (shear strength). In order to effectively avoid the above-mentioned circuit peeling, it is required to maintain the shear strength above a certain level. However, in order to ensure a shear strength above a certain level, the roughening particles of the copper foil have to be increased, and there is a problem that it is difficult to achieve a balance with the etching property.
[0011] The present inventors have now obtained the following insight: by giving a surface profile in which the interface extension area ratio Sdr and the level difference Sk of the center portion specified in ISO25178 are respectively controlled within the specified ranges in the roughened copper foil, it is possible to achieve both excellent etching resistance and high shear strength in the processing of copper-clad laminates and / or the manufacture of printed circuit boards.
[0012] Therefore, an object of the present invention is to provide a roughened copper foil that can achieve both excellent etching properties and high shear strength in the processing of a copper-clad laminate and / or the production of a printed wiring board.
[0013] According to one embodiment of the present invention, there is provided a roughened copper foil having a roughened surface on at least one side.
[0014] The interface extension area ratio Sdr of the roughened surface measured in accordance with ISO25178 under the conditions of a cutoff wavelength of 0.55 μm based on the S filter and a cutoff wavelength of 10 μm based on the L filter is 3.50% or more and 12.00% or less, and the level difference Sk of the center portion measured in accordance with ISO25178 under the conditions of a cutoff wavelength of 0.55 μm based on the S filter and a cutoff wavelength of 10 μm based on the L filter is 0.15 μm or more and 0.35 μm or less.
[0015] According to another aspect of the present invention, there is provided a copper foil with a carrier, comprising: a carrier, a release layer provided on the carrier, and the roughened copper foil provided on the release layer with the roughened surface facing the outside.
[0016] According to another aspect of the present invention, there is provided a copper-clad laminate including the roughened copper foil.
[0017] According to another aspect of the present invention, there is provided a printed wiring board including the roughened copper foil. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 This is a process flow chart for explaining the MSAP method, and is a diagram showing the first half of the steps (steps (a) to (d)).
[0019] Figure 2 This is a process flow chart for explaining the MSAP method, and is a diagram showing the latter half of the process (processes (e) to (g)).
[0020] Figure 3 This is a diagram for explaining the load curve and load area ratio determined in accordance with ISO25178.
[0021] Figure 4 This is a diagram for explaining the load area ratio Smr1 separating the protruding peak portion and the center portion, the load area ratio Smr2 separating the protruding valley portion and the center portion, and the level difference Sk of the center portion, which are determined based on ISO25178.
[0022] Figure 5 This is a schematic cross-sectional view showing an example of a laminate for evaluation before etching in circuit formability (etching property evaluation).
[0023] Figure 6 This is a schematic diagram for explaining the method of measuring shear strength. DETAILED DESCRIPTION
[0024] definition
[0025] Definitions of terms and / or parameters used to define the present invention are shown below.
[0026] In this specification, "interface expansion area ratio Sdr" refers to: a parameter measured in accordance with ISO25178, which indicates how much the expansion area (surface area) of a defined area increases relative to the area of the defined area. It should be noted that in this specification, the interface expansion area ratio Sdr is expressed as the increase in the surface area (%). The smaller the value, the closer the surface shape is to being flat, and the Sdr of a completely flat surface is 0%. On the other hand, the larger the value, the more uneven the surface shape is. For example, when the Sdr of a surface is 40%, it means that the surface area of the surface has increased by 40% from a completely flat surface.
[0027] In this specification, the "surface load curve" (hereinafter referred to as "load curve") refers to a curve indicating the height of the load area ratio from 0% to 100% measured in accordance with ISO25178. Figure 3 The following are parameters that represent the area of the area above a certain height c. The load area ratio at height c is equivalent to Figure 3 Smr(c) in Figure 4 As shown in FIG. 1 , a secant line of the load curve is drawn from the load area rate of 0% with the load area rate difference set to 40%, and the secant line of the load curve is moved from the load area rate of 0%. The position where the slope of the secant line is the most gentle is called the central part of the load curve. With respect to the central part, the straight line with the smallest sum of the squares of the deviations from the vertical axis direction is called the equivalent straight line. The portion of the equivalent straight line included in the range of the height of the load area rate of 0% to 100% is called the central part. The portion higher than the central part is called the protruding peak, and the portion lower than the central part is called the protruding valley.
[0028] In this specification, the "center level difference Sk" is the value obtained by subtracting the minimum height from the maximum height of the center, as measured in accordance with ISO25178. Figure 4 The figure shows the parameters calculated by the height difference between the load area ratio of 0% and 100% passing through the equivalent straight line.
[0029] In this specification, the "maximum height Sz" is a parameter indicating the distance from the highest point to the lowest point of the surface measured in accordance with ISO25178.
[0030] In this specification, "surface aspect ratio Str" is a parameter indicating the isotropy and / or anisotropy of the surface texture, measured according to ISO 25178. Str ranges from 0 to 1, and Str>0.5 generally indicates strong isotropy, whereas Str<0.3 indicates strong anisotropy.
[0031] In this specification, "peak apex density Spd" is a parameter indicating the number of peak apexes per unit area measured in accordance with ISO 25178, and only peak apexes larger than 5% of the maximum amplitude of the contour surface are counted. A larger value indicates a greater number of contact points with other objects.
[0032] The interface expansion area ratio Sdr, the level difference Sk at the center, the maximum height Sz, the aspect ratio Str of the surface properties, and the peak apex density Spd can be determined by measuring a predetermined measurement area (e.g., 16384 μm) of the roughened surface using a commercially available laser microscope. 2 The surface profile of the two-dimensional region (two-dimensional region) is measured and calculated respectively. In this specification, the numerical values of the interface expansion area ratio Sdr, the level difference Sk of the center part, the maximum height Sz and the aspect ratio Str of the surface properties are measured under the conditions of a cutoff wavelength of 0.55 μm based on the S filter and a cutoff wavelength of 10 μm based on the L filter. In addition, in this specification, the numerical value of the peak vertex density Spd is measured under the conditions of a cutoff wavelength of 3 μm based on the S filter and a cutoff wavelength of 10 μm based on the L filter.
[0033] In this specification, the "electrode surface" of a carrier refers to the surface on the side in contact with the cathode when the carrier is produced.
[0034] In this specification, the "deposition surface" of the carrier refers to the surface on the side where electrolytic copper is deposited when the carrier is produced, that is, the surface on the side not in contact with the cathode.
[0035] Roughened copper foil
[0036] The copper foil of the present invention is a roughened copper foil. The roughened copper foil has a roughened surface on at least one side. The interface expansion area ratio Sdr of the roughened surface is greater than 3.50% and less than 12.00%, and the level difference Sk of the center portion is greater than 0.15 μm and less than 0.35 μm. In this way, by giving the roughened copper foil a surface profile in which the interface expansion area ratio Sdr and the level difference Sk of the center portion are respectively controlled to a specified range, it is possible to achieve both excellent etching properties and high shear strength in the processing of copper-clad laminates and / or the manufacture of printed circuit boards.
[0037] Excellent etching property and high shear strength are difficult to take into account. This is because, as mentioned above, in order to improve the etching property of copper foil, it is usually required to reduce the roughening particles. On the other hand, in order to improve the shear strength of the circuit, it is usually required to increase the roughening particles. In particular, the shear strength is not simply proportional to the specific surface area, roughening height, etc. used in the evaluation in the past, and it is difficult to control it. For this point, the inventors found that in order to obtain the correlation with the physical properties such as etching property and shear strength, it is effective to evaluate the combination of the interface expansion area ratio Sdr and the horizontal difference Sk of the center. Moreover, it is found that by controlling these surface parameters to be within the above-mentioned specified range, a roughening copper foil with a fine surface excellent in etching property and a protrusion height and a specific surface area suitable for ensuring high shear strength can be obtained. In this way, using the roughening copper foil of the present invention, excellent etching property and high shear strength can be achieved, and therefore, high circuit adhesion under the viewpoint of excellent fine circuit formation and shear strength can be taken into account. It should be noted that in the past, it is known that there is a technology for controlling the extended area ratio Sdr, the root mean square slope Sdq and the aspect ratio Str of the surface properties of the surface treated copper foil (see the above-mentioned patent document 1). However, these parameters are all parameters obtained by including the protruding peak. If the generation of the protruding peak is suppressed, there is a situation where the values become too small. In contrast, the present inventors have obtained the following insights: by controlling the level difference Sk of the center portion of the parameter not including the protruding peak and the extended area ratio Sdr of the parameter including the protruding peak, respectively, so that the generation of the protruding peak can be suppressed for the roughening surface, and each roughening particle constituting the roughening surface is uniformly embedded in the resin, thereby obtaining a roughening copper foil having a protrusion height and specific surface area suitable for ensuring high shear strength even if it is a fine surface with excellent etching performance.
[0038] From the viewpoint of achieving excellent etching properties and high shear strength in a well-balanced manner, the interface expansion area ratio Sdr of the roughened surface of the roughened copper foil is 3.50% or more and 12.00% or less, preferably 4.50% or more and 8.50% or less, and more preferably 4.50% or more and 6.00% or less. If it is within such a range, even if it is a fine surface (roughening height) with excellent etching properties, it is possible to ensure sufficient bonding area with the laminated resin during the manufacture of the copper-clad laminate and / or printed circuit board, and the circuit adhesion from the viewpoint of shear strength is improved.
[0039] From the viewpoint of achieving excellent etching property and high shear strength in a well-balanced manner, the level difference Sk of the center portion of the roughening surface of the roughening copper foil is 0.15 μm or more and 0.35 μm or less, preferably 0.23 μm or more and 0.35 μm or less, more preferably 0.25 μm or more and 0.35 μm or less. If it is within such a range, even if it is a fine surface (roughening height) with excellent etching property, each roughening particle constituting the roughening surface can be evenly embedded in the resin, and as a result, the adhesion with the resin is improved. That is, it is believed that if the roughening treatment is uneven, the unevenness will become the protruding peak of the roughening surface. However, such unevenness (protruding peak) is difficult to help the improvement of circuit adhesion under the viewpoint of shear strength. For this point, the maximum height Sz used in the previous evaluation is a parameter including a protruding peak. Therefore, in the case of wanting to achieve the improvement of circuit adhesion based on such parameters, the roughening height is easy to become larger, so the etching property is easy to reduce. In contrast, the level difference Sk of the center portion is a parameter that does not include a protruding peak portion as described above. Therefore, by using the level difference Sk of the center portion as an evaluation index, the surface shape most suitable for improving the adhesion with the resin can be accurately obtained, and as a result, the increase in the roughening height can be suppressed.
[0040] The ratio of the level difference Sk (μm) of the center portion of the roughened surface of the roughened copper foil to the interface extension area ratio Sdr (%), i.e., Sk / Sdr, is preferably 0.038 or more and 0.050 or less, and more preferably 0.045 or more and 0.050 or less. If it is within such a range, the height unevenness is further reduced for the concave-convex shape of the roughened surface, and not only the concave-convex shape of the roughened surface is large (i.e., the surface area is large), but also the height of the center portion can be fully ensured. That is, the level difference Sk of the center portion is a parameter obtained by removing the protruding peaks, and the extension area ratio Sdr is a parameter obtained by including the protruding peaks. Therefore, when the number of protruding peaks increases or decreases, the value of the level difference Sk of the center portion is constant, but the value of the extension area ratio Sdr will change. Therefore, by controlling the ratio of the level difference Sk of the center portion to the extended area ratio Sdr within the above range, the generation of protruding peaks can be suppressed for the roughened surface, thereby making it easy for each roughened particle constituting the roughened surface to be uniformly embedded in the resin. As a result, excellent etching resistance and high shear strength can be achieved in a more balanced manner.
[0041] In the roughened copper foil, the product of the maximum height Sz (μm) of the roughened surface and the level difference Sk (μm) of the center, i.e., Sz×Sk, is preferably 0.25 or more and 0.50 or less, and more preferably 0.36 or more and 0.50 or less. If it is within such a range, the generation of protruding peaks of the concave-convex shape of the roughened surface can be further suppressed, which is more suitable for achieving excellent etching properties and high shear strength in a well-balanced manner. In addition, from the perspective of achieving a fine surface with better etching properties, the maximum height Sz of the roughened surface of the roughened copper foil is preferably 1.6μm or less, more preferably 1.0μm or more and 1.4μm or less, and further preferably 1.0μm or more and 1.2μm or less.
[0042] The peak apex density Spd of the roughened surface of the roughened copper foil is preferably 2.00×10 4 mm -2 Above and 3.00×10 4 mm -2 Below, more preferably 2.20×10 4 mm -2 Above and 3.00×10 4 mm -2 Below, more preferably 2.75×10 4 mm -2 Above and 2.85×10 4 mm -2 By doing so, sufficient bonding points with the laminated resin can be ensured during the production of the copper-clad laminate and / or printed wiring board, and circuit adhesion from the viewpoint of shear strength can be more effectively improved.
[0043] The aspect ratio Str of the surface properties of the roughened copper foil is preferably 0.2 to 0.5, more preferably 0.24 to 0.50, and further preferably 0.45 to 0.50. If it is within such a range, there will be a waviness suitable for adhesion with resin on the roughened surface. As a result, even if it is a fine surface with excellent etching properties, the circuit adhesion from the perspective of shear strength can be more effectively improved.
[0044] The thickness of the roughened copper foil is not particularly limited, and is preferably 0.1 μm or more and 35 μm or less, more preferably 0.5 μm or more and 5.0 μm or less, and further preferably 1.0 μm or more and 3.0 μm or less. It should be noted that the roughened copper foil is not limited to the surface of the conventional copper foil, but may be the surface of the copper foil of the copper foil with a carrier. Here, the thickness of the roughened copper foil is the thickness of the height of the roughened particles formed on the surface of the roughened surface (the thickness of the copper foil itself constituting the roughened copper foil). Copper foil having the above-mentioned range of thickness is sometimes referred to as ultra-thin copper foil.
[0045] The roughened copper foil has a roughened surface on at least one side. That is, the roughened copper foil may have a roughened surface on both sides or only on one side. The roughened surface is typically formed with a plurality of roughened particles (protrusions), and each of these plurality of roughened particles is preferably formed of copper particles. The copper particles may be formed of metallic copper or of a copper alloy.
[0046] The roughening treatment for forming the roughened surface can be more preferably performed by forming roughened particles on the copper foil using copper or a copper alloy. For example, the roughening treatment is preferably performed by a method of at least two plating steps, wherein the plating steps include: a sintering step for causing fine copper particles to precipitate and adhere to the copper foil; and a coating plating step for preventing the fine copper particles from falling off. In this case, the sintering step is preferably: in a copper sulfate solution containing a copper concentration of 5 g / L or more and 20 g / L or less and a sulfuric acid concentration of 180 g / L or more and 240 g / L or less, carboxybenzotriazole (CBTA) is added in a concentration of 20 ppm or more and 29 ppm or less, at a temperature of 15°C or more and 35°C or less and at 14 A / dm 2 Above and 24A / dm 2 The electroplating step is preferably performed in a copper sulfate solution containing a copper concentration of 50 g / L to 100 g / L and a sulfuric acid concentration of 200 g / L to 250 g / L, at a temperature of 40°C to 60°C and at 2 A / dm 2 Above and 4A / dm 2Electrodeposition is then performed. In particular, in the calcination step, by adding carboxybenzotriazole within the above concentration range to the plating solution, the formation of protruding peaks on the roughened surface can be suppressed while maintaining etching properties close to that of pure copper, and each roughening particle constituting the roughened surface is uniformly embedded in the resin, making it easy to form protrusions on the treated surface that meet the above surface parameters. Furthermore, in the calcination step and the coating plating step, the electrodeposition is performed by lowering the current density than in the conventional method, thereby making it easier to form protrusions on the treated surface that meet the above surface parameters.
[0047] According to the expectation, the roughened copper foil can be subjected to rust-proof treatment to form a rust-proof treatment layer. The rust-proof treatment preferably includes a plating treatment using zinc. The plating treatment using zinc can be any of the zinc plating treatment and the zinc alloy plating treatment, and the zinc alloy plating treatment is particularly preferably a zinc-nickel alloy treatment. The zinc-nickel alloy treatment can be a plating treatment containing at least Ni and Zn, and can also contain other elements such as Sn, Cr, and Co. The Ni / Zn adhesion ratio in the zinc-nickel alloy plating is preferably 1.2 or more and 10 or less, more preferably 2 or more and 7 or less, and further preferably 2.7 or more and 4 or less in terms of mass ratio. In addition, the rust-proof treatment preferably also includes a chromate treatment, and the chromate treatment is more preferably performed on the surface of the zinc-containing coating after the zinc plating treatment. In this way, the rust resistance can be further improved. A particularly preferred rust-proof treatment is a combination of a zinc-nickel alloy plating treatment and a subsequent chromate treatment.
[0048] According to the expectation, the roughened copper foil can be treated with a silane coupling agent on the surface to form a silane coupling agent layer. This can improve moisture resistance, chemical resistance, and adhesion to adhesives, etc. The silane coupling agent layer can be formed by appropriately diluting and applying the silane coupling agent and drying it. Examples of silane coupling agents include epoxy-functional silane coupling agents such as 4-glycidoxybutyltrimethoxysilane and 3-glycidoxypropyltrimethoxysilane, or 3-aminopropyltrimethoxysilane, N-(2-aminoethyl)-3-aminopropyltrimethoxysilane, N-3-(4-(3-aminopropoxy)butoxy)propyl-3-aminopropyltrimethoxysilane, N-phenyl-3-aminopropyl The present invention can be used as the silane coupling agent of claim 1, wherein the silane coupling agent comprises an amino-functional silane coupling agent such as trimethoxy silane, a mercapto-functional silane coupling agent such as 3-mercaptopropyltrimethoxy silane, an olefin-functional silane coupling agent such as vinyltrimethoxy silane and vinylphenyltrimethoxy silane, an acrylic-functional silane coupling agent such as 3-methacryloxypropyltrimethoxy silane, an imidazole-functional silane coupling agent such as imidazole silane, or a triazine-functional silane coupling agent such as triazine silane.
[0049] Based on the above reasons, the roughened copper foil preferably has an anti-rust treatment layer and / or a silane coupling agent layer on the roughened surface, and more preferably has both an anti-rust treatment layer and a silane coupling agent layer. The anti-rust treatment layer and the silane coupling agent layer can be formed not only on the roughened surface side of the roughened copper foil, but also on the side where the roughened surface is not formed.
[0050] Copper foil with carrier
[0051] As described above, the roughened copper foil of the present invention can be provided in the form of a copper foil with a carrier. That is, according to a preferred embodiment of the present invention, a copper foil with a carrier is provided, which comprises: a carrier, a peeling layer provided on the carrier, and the roughened copper foil provided on the peeling layer with the roughened surface as the outer side. Of course, in addition to using the roughened copper foil of the present invention, the copper foil with a carrier can also adopt a known layer structure.
[0052] The carrier is a support for supporting the roughened copper foil to improve its handleability, and a typical carrier includes a metal layer. Examples of such carriers include aluminum foil, copper foil, stainless steel (SUS) foil, resin films coated with metal on the surface with copper, etc., glass, etc., preferably copper foil. The copper foil can be any of rolled copper foil and electrolytic copper foil. Preferably, electrolytic copper foil. The thickness of the carrier is typically 250 μm or less, preferably 9 μm or more and 200 μm or less.
[0053] The surface on the peeling layer side of the carrier is preferably smooth. That is, in the manufacturing process of the copper foil with a carrier, an extremely thin copper foil (before roughening treatment) is formed on the surface of the peeling layer side of the carrier. In the case of using the roughened copper foil of the present invention in the form of a copper foil with a carrier, the roughened copper foil can be obtained by roughening such an extremely thin copper foil. Therefore, by smoothing the surface on the peeling layer side of the carrier in advance, the outer surface of the extremely thin copper foil can also be smoothed, and by roughening the smooth surface of the extremely thin copper foil, it becomes easy to achieve a roughened surface having an interface expansion area ratio Sdr and a level difference Sk of the center portion within the above-mentioned specified range. When smoothing the surface on the peeling layer side of the carrier, for example, it can be done by grinding the surface of the cathode used when the carrier is electrolytically made into foil with a polishing wheel of a specified model to adjust the surface roughness. That is, the surface profile of the cathode adjusted in this way is transferred to the electrode surface of the carrier, and by forming an ultra-thin copper foil on the electrode surface of the carrier via the release layer, the outer surface of the ultra-thin copper foil can be given a smooth surface state that is easy to achieve the above-mentioned roughening treatment surface. The preferred model of the polishing wheel is greater than #2000 and less than #3000, and more preferably greater than #2000 and less than #2500.
[0054] The peeling layer is a layer having the following functions: weakening the peeling strength of the carrier, ensuring the stability of the strength, and further inhibiting the mutual diffusion that may be caused between the carrier and the copper foil during press forming at high temperature. The peeling layer is usually formed on one side of the carrier, but it can also be formed on both sides. The peeling layer can be any of an organic peeling layer and an inorganic peeling layer. Examples of organic components used in the organic peeling layer include nitrogen-containing organic compounds, sulfur-containing organic compounds, carboxylic acids, etc. Examples of nitrogen-containing organic compounds include triazole compounds and imidazole compounds, among which triazole compounds are preferred from the perspective of easy and stable peeling properties. Examples of triazole compounds include 1,2,3-benzotriazole, carboxybenzotriazole, N',N'-bis(benzotriazolylmethyl)urea, 1H-1,2,4-triazole and 3-amino-1H-1,2,4-triazole, etc. Examples of sulfur-containing organic compounds include mercaptobenzothiazole, trithiocyanate, 2-benzimidazolethiol, etc. As examples of carboxylic acids, monocarboxylic acids, dicarboxylic acids, etc. can be cited. On the other hand, as examples of inorganic components used in the inorganic peeling layer, Ni, Mo, Co, Cr, Fe, Ti, W, P, Zn, chromate treatment films, etc. can be cited. It should be noted that the formation of the peeling layer can be carried out by bringing a solution containing peeling layer components into contact with at least one surface of the carrier, fixing the peeling layer components on the surface of the carrier, etc. In the case of bringing the carrier into contact with a solution containing peeling layer components, the contact can be carried out by immersion in a solution containing peeling layer components, spraying of a solution containing peeling layer components, and flow of a solution containing peeling layer components. In addition, a method of forming a film by coating the peeling layer components by a vapor phase method based on evaporation, sputtering, etc. can also be adopted. In addition, the fixing of the peeling layer components to the surface of the carrier can be carried out by adsorption, drying, and electrodeposition of the peeling layer components in a solution containing peeling layer components. The thickness of the peeling layer is typically 1 nm or more and 1 μm or less, preferably 5 nm or more and 500 nm or less.
[0055] As desired, other functional layers may be provided between the peeling layer and the carrier and / or the roughened copper foil. As examples of such other functional layers, auxiliary metal layers may be cited. The auxiliary metal layer is preferably formed of nickel and / or cobalt. By forming such an auxiliary metal layer on the surface side of the carrier and / or the surface side of the roughened copper foil, it is possible to suppress the mutual diffusion that may be caused between the carrier and the roughened copper foil during hot pressing at high temperatures or for a long time, and to ensure the stability of the peel strength of the carrier. The thickness of the auxiliary metal layer is preferably set to be greater than 0.001 μm and less than 3 μm.
[0056] Copper Clad Laminated Board
[0057] The roughened copper foil of the present invention is preferably used for the production of copper-clad laminates for printed circuit boards. That is, according to a preferred embodiment of the present invention, a copper-clad laminate is provided, which has the above-mentioned roughened copper foil. By using the roughened copper foil of the present invention, excellent etching resistance and high shear strength can be taken into account in the processing of the copper-clad laminate. The copper-clad laminate comprises: the roughened copper foil of the present invention, and a resin layer tightly arranged on the roughened surface of the roughened copper foil. The roughened copper foil can be arranged on one side of the resin layer or on both sides. The resin layer contains a resin, preferably an insulating resin. The resin layer is preferably a prepreg and / or a resin sheet. Prepreg refers to a general term for composite materials impregnated with synthetic resins in substrates such as synthetic resin plates, glass plates, glass woven fabrics, glass non-woven fabrics, and paper. As preferred examples of insulating resins, epoxy resins, cyanate resins, bismaleimide triazine resins (BT resins), polyphenylene ether resins, phenolic resins, etc. can be cited. In addition, as examples of insulating resins constituting the resin sheet, insulating resins such as epoxy resins, polyimide resins, and polyester resins can be cited. In addition, from the viewpoint of improving insulation, the resin layer may contain filler particles containing various inorganic particles such as silica and alumina. The thickness of the resin layer is not particularly limited, preferably 1 μm or more and 1000 μm or less, more preferably 2 μm or more and 400 μm or less, and further preferably 3 μm or more and 200 μm or less. The resin layer may be composed of a plurality of layers. Resin layers such as prepregs and / or resin sheets may be provided on the roughened copper foil via a primer resin layer pre-coated on the surface of the copper foil.
[0058] Printed Circuit Board
[0059] The roughened copper foil of the present invention is preferably used for the production of printed circuit boards. That is, according to a preferred embodiment of the present invention, a printed circuit board is provided, which has the above-mentioned roughened copper foil. By using the roughened copper foil of the present invention, excellent etching resistance and high shear strength can be taken into account in the manufacture of printed circuit boards. The printed circuit board of this embodiment comprises a layer structure stacked with a resin layer and a copper layer. The copper layer is a layer derived from the roughened copper foil of the present invention. In addition, for the resin layer, as described above with respect to the copper-clad laminate. In any case, in addition to using the roughened copper foil of the present invention, the printed circuit board can adopt a known layer structure. As a specific example related to the printed circuit board, the single-sided or double-sided printed circuit board obtained by bonding the roughened copper foil of the present invention to one or both sides of the prepreg and curing to form a laminate and then forming a circuit, and the multilayer printed circuit board formed by multilayering them, etc. can be listed. In addition, as other specific examples, flexible printed circuit boards, COFs, TAB tapes, etc., which form circuits by forming the roughened copper foil of the present invention on a resin film, can also be listed. As other specific examples, there can be listed: a resin-coated copper foil (RCC) formed by coating the above-mentioned resin layer on the roughened copper foil of the present invention, a build-up wiring board in which a circuit is formed by a modified semi-additive (MSAP) method, a subtractive method, or the like after laminating the resin layer as an insulating adhesive layer on the above-mentioned printed circuit board, and then using the roughened copper foil as all or part of the wiring layer, a build-up wiring board in which the roughened copper foil is removed and a circuit is formed by a semi-additive method, and a direct build-up wafer (direct build up on wafer) in which the lamination of the resin-coated copper foil on a semiconductor integrated circuit and the formation of the circuit are repeated alternately. As further developed specific examples, there can also be listed antenna elements in which the above-mentioned resin-coated copper foil is laminated on a substrate to form a circuit, electronic materials for panels and displays that are laminated on glass and resin films with the aid of an adhesive layer to form a pattern, electronic materials for window glass, and electromagnetic wave shielding films obtained by coating a conductive adhesive on the roughened copper foil of the present invention. In particular, the roughened copper foil of the present invention is suitable for the MSAP method. For example, in the case of forming a circuit by the MSAP method, it is possible to use Figure 1 and 2 The structure shown.
[0060] Example
[0061] The present invention is described in more detail by the following examples.
[0062] Examples 1 to 7, 9 and 10
[0063] A copper foil with a carrier having a roughened copper foil was prepared and evaluated as follows.
[0064] (1) Preparation of vector
[0065] The copper electrolyte solution with the following composition, cathode and DSA (dimensional stability anode) as anode were used, and the solution temperature was 50° C. and the current density was 70 A / dm 2 Electrolysis was performed to prepare an electrolytic copper foil having a thickness of 18 μm as a carrier. At this time, an electrode whose surface roughness was adjusted by grinding it with a #2000 buff was used as a cathode.
[0066] <Composition of copper electrolyte>
[0067] -Copper concentration: 80g / L
[0068] - Sulfuric acid concentration: 300g / L
[0069] -Chlorine concentration: 30mg / L
[0070] -Glue concentration: 5mg / L
[0071] (2) Formation of the peeling layer
[0072] The electrode surface of the support treated with acid washing was immersed in a CBTA aqueous solution containing a carboxybenzotriazole (CBTA) concentration of 1 g / L, a sulfuric acid concentration of 150 g / L, and a copper concentration of 10 g / L at a liquid temperature of 30° C. for 30 seconds to allow the CBTA component to be adsorbed on the electrode surface of the support. In this way, a CBTA layer was formed on the electrode surface of the support as an organic release layer.
[0073] (3) Formation of auxiliary metal layer
[0074] The support having the organic release layer formed thereon was immersed in a solution containing 20 g / L of nickel prepared by using nickel sulfate, and the mixture was stirred at a temperature of 45°C, a pH of 3, and a current density of 5 A / dm 2 Under the conditions of , nickel in an amount corresponding to a thickness of 0.001 μm was deposited on the organic release layer. Thus, a nickel layer was formed on the organic release layer as an auxiliary metal layer.
[0075] (4) Formation of ultra-thin copper foil
[0076] The support having the auxiliary metal layer formed thereon was immersed in a copper solution of the composition shown below at a solution temperature of 50° C. and a current density of 5 A / dm 2 Above and 30A / dm 2 Next, electrolysis was performed to form an ultra-thin copper foil having a thickness of 1.5 μm on the auxiliary metal layer.
[0077] <Solution Composition>
[0078] -Copper concentration: 60g / L
[0079] - Sulfuric acid concentration: 200g / L
[0080] (5) Roughening treatment
[0081] The surface of the ultra-thin copper foil thus formed is roughened to form a roughened copper foil, thereby obtaining a copper foil with a carrier. The roughening treatment consists of a sintering process for precipitating and attaching fine copper particles on the ultra-thin copper foil and a coating plating process for preventing the fine copper particles from falling off. In the sintering process, carboxylbenzotriazole (CBTA) of the concentration shown in Table 1 is added to an acidic copper sulfate solution containing a copper concentration of 10 g / L and a sulfuric acid concentration of 200 g / L at a liquid temperature of 25°C, and the roughening treatment is performed at the current density shown in Table 1. In the subsequent coating plating process, an acidic copper sulfate solution containing a copper concentration of 70 g / L and a sulfuric acid concentration of 240 g / L is used to perform electrodeposition under smooth plating conditions of a liquid temperature of 52°C and a current density shown in Table 1. At this time, the CBTA concentration and current density in the sintering process, and the current density in the coating plating process are appropriately changed as shown in Table 1, thereby preparing various samples with different characteristics of the roughened surface.
[0082] (6) Anti-rust treatment
[0083] The roughened surface of the copper foil with carrier was subjected to rust prevention treatment including zinc-nickel alloy plating and chromate treatment. First, a solution containing 1 g / L zinc, 2 g / L nickel and 80 g / L potassium pyrophosphate was used at a liquid temperature of 40°C and a current density of 0.5 A / dm 2 The surface of the roughened layer and the carrier was subjected to zinc-nickel alloy plating under the conditions of 1.5 % and 1.5 % respectively. Then, an aqueous solution containing 1 g / L of chromic acid was used at pH 12 and a current density of 1 A / dm 2 The surface treated with zinc-nickel alloy plating was chromated under the conditions of.
[0084] (7) Silane coupling agent treatment
[0085] The silane coupling agent treatment was performed by adsorbing an aqueous solution containing a commercially available silane coupling agent on the surface of the roughened copper foil side of the copper foil with a carrier, and evaporating the water with an electric heater. At this time, the carrier side was not treated with the silane coupling agent.
[0086] (8) Evaluation
[0087] The copper foil with a carrier obtained in this manner was evaluated for various properties as follows.
[0088] (8a) Surface properties parameters of the roughened surface
[0089] The surface roughness of the roughened copper foil was measured by surface roughness analysis using a laser microscope (manufactured by Olympus Corporation, OLS5000) in accordance with ISO 25178. Specifically, the roughened copper foil was subjected to a 16384 μm surface roughness test using a 100x lens with an aperture ratio (NA) of 0.95 using the laser microscope. 2 The surface profile of the area is measured. After the surface profile of the roughened surface is subjected to noise removal and first-order linear surface tilt correction, the maximum height Sz, the interface expansion area ratio Sdr, the aspect ratio Str of the surface properties, the level difference Sk of the center, and the peak vertex density Spd are measured by surface property analysis. At this time, for the measurement of Sz, Sdr, Str and Sk, the cutoff wavelength based on the S filter is set to 0.55μm, and the cutoff wavelength based on the L filter is set to 10μm for measurement. On the other hand, for the measurement of Spd, the cutoff wavelength based on the S filter is set to 3μm, and the cutoff wavelength based on the L filter is set to 10μm for measurement. The results are shown in Table 1.
[0090] (8b) Circuit Formability (Evaluation of Etching Properties)
[0091] The obtained copper foil with carrier was used to prepare a laminate for evaluation. Figure 5 As shown, a roughened copper foil 110 with a carrier is laminated on the surface of an insulating resin substrate 111 through a prepreg 112 (manufactured by Mitsubishi Gas Chemical Co., Ltd., GHPL-830NSF, thickness 0.1 mm), and after hot pressing for 90 minutes at a pressure of 4.0 MPa and a temperature of 220°C, the carrier (not shown) is peeled off to obtain a copper-clad laminate 114 as an evaluation laminate. Figure 5 In the example shown, the roughened copper foil 110 has roughened particles 110a on its surface. It should be noted that the required etching amount varies according to the thickness of the ultra-thin copper foil for etching evaluation. Figure 5As shown, in order to make the thickness of the roughened copper foil 110 in the evaluation laminate 114 equivalent to 1.5 μm (excluding the thickness of the roughened particles 110a), the evaluation laminate 114 is reduced in thickness based on half etching and / or increased in thickness based on copper sulfate plating as needed. For the evaluation laminate 114 whose thickness of the roughened copper foil 110 is adjusted to 1.5 μm, etching is performed at 0.1 μm each time with a sulfuric acid-hydrogen peroxide etching solution, and the amount (depth) until the copper on the surface (including the roughened particles 110a) completely disappears is measured. The measurement is performed by confirming with an optical microscope (500 times). In more detail, the operation of confirming the presence or absence of copper with an optical microscope every time etching 0.1 μm is repeated, and the value (μm) obtained by (number of etchings) × 0.1 μm is used as an indicator of etching properties. For example, an etching property of 2.5 μm means that after 25 times of etching at 0.1 μm, no residual copper is detected by an optical microscope (i.e., 0.1 μm × 25 times = 2.5 μm). That is, the smaller the value, the more copper on the surface can be removed with fewer etchings. That is, the smaller the value, the better the etching property. The measured etching amount is graded and evaluated according to the following criteria, and any case of evaluation A to C is judged to be qualified. The results are shown in Table 1.
[0092] <Evaluation Criteria for Etching Properties>
[0093] -Evaluation A: The required etching amount is 2.3 μm or less
[0094] -Evaluation B: The required etching amount is more than 2.3 μm and less than 2.5 μm
[0095] -Evaluation C: The required etching amount is more than 2.5 μm and less than 2.7 μm
[0096] - Rating D: The required etching amount exceeds 2.7 μm
[0097] (8c) Plated circuit adhesion (shear strength)
[0098] The dry film was attached to the evaluation laminated body, and then exposed and developed. After a copper layer with a thickness of 14 μm was deposited by pattern plating on the laminated body masked with the developed dry film, the dry film was peeled off. The exposed copper portion was etched with a sulfuric acid-hydrogen peroxide etching solution to prepare a circuit sample for shear strength measurement with a height of 15 μm, a width of 10 μm, and a length of 200 μm ( Figure 6 The shear strength of the circuit 136 was measured by pushing the circuit 136 from the side of the circuit sample for shear strength measurement and causing it to deflect using a bonding strength tester (4000Plus Bondtester manufactured by Nordson DAGE). Figure 6As shown, a laminate 134 formed with a circuit 136 is placed on a movable stage 132, and the stage 132 is moved in the direction of the arrow in the figure, and the circuit 136 is pressed against a pre-fixed detector 138, thereby applying a lateral force to the side of the circuit 136, causing the circuit 136 to shift laterally, and the force (gf) at this time is measured by the detector 138 and used as the shear strength. At this time, the test type is set as a destructive test, and the test is performed under the conditions of a test height of 5μm, a descent speed of 0.050mm / s, a test speed of 200μm / s, a tool movement of 0.05mm, and a destruction identification point of 10%. The obtained shear strength is graded and evaluated according to the following criteria, and any of the evaluations A to C is judged to be qualified. The results are shown in Table 1.
[0099] <Shear Strength Evaluation Criteria>
[0100] -Evaluation A: Shear strength is 13.50 gf or more
[0101] -Evaluation B: Shear strength is 12.50 gf or more and less than 13.50 gf
[0102] -Evaluation C: Shear strength is 12.00 gf or more and less than 12.50 gf
[0103] - Rating D: Shear strength less than 12.00 gf
[0104] Example 8 (Compare)
[0105] The copper foil with a carrier was prepared and evaluated in the same manner as in Example 1 except for the following a) to c).
[0106] a) Prepare the vector according to the steps shown below.
[0107] b) Instead of the electrode surface of the carrier, a release layer, an auxiliary metal layer and an ultra-thin copper foil are sequentially formed on the deposition surface of the carrier.
[0108] c) The ultra-thin copper foil is roughened by the black plating step described below instead of the baking plating step and the cover plating step.
[0109] (Preparation of vector)
[0110] A sulfuric acid copper sulfate solution with the composition shown below was used as the copper electrolyte, a titanium electrode with a surface roughness Ra of 0.20 μm was used as the cathode, and a DSA (dimensionally stable anode) was used as the anode. The solution temperature was 45°C and the current density was 55 A / dm 2 Electrolysis was performed under the conditions of 100 μm to obtain an electrolytic copper foil with a thickness of 12 μm as a carrier.
[0111] <Composition of sulfuric acid-acid copper sulfate solution>
[0112] -Copper concentration: 80g / L
[0113] - Sulfuric acid concentration: 140g / L
[0114] - Bis(3-sulfopropyl) disulfide concentration: 30mg / L
[0115] -Diallyldimethylammonium chloride polymer concentration: 50mg / L
[0116] -Chlorine concentration: 40mg / L
[0117] (Black plating process)
[0118] The surface of the ultra-thin copper foil was subjected to a black roughening copper electrolytic solution with the following composition at a solution temperature of 30°C and a current density of 50 A / dm 2 Electrolysis is carried out under the conditions of 4 seconds and black roughening is performed.
[0119] <Composition of copper electrolytic solution for black roughening>
[0120] -Copper concentration: 13g / L
[0121] - Sulfuric acid concentration: 70g / L
[0122] -Chlorine concentration: 35mg / L
[0123] -Sodium polyacrylate concentration: 400ppm
[0124] [Table 1]
[0125]
Claims
1. A roughened copper foil having a roughened surface on at least one side, The interface extension area ratio Sdr of the roughened surface measured according to ISO25178 under the conditions of a cutoff wavelength of 0.55 μm based on the S filter and a cutoff wavelength of 10 μm based on the L filter is 3.50% or more and 12.00% or less, and the level difference Sk of the center portion measured according to ISO25178 under the conditions of a cutoff wavelength of 0.55 μm based on the S filter and a cutoff wavelength of 10 μm based on the L filter is 0.15 μm or more and 0.35 μm or less.
2. The roughened copper foil according to claim 1, wherein: The ratio of the level difference Sk of the center portion in μm to the interface extension area ratio Sdr in %, that is, Sk / Sdr, is 0.038 or more and 0.050 or less.
3. The roughened copper foil according to claim 1 or 2, wherein: The product of the maximum height Sz of the roughened surface in μm measured under the conditions of a cutoff wavelength of 0.55 μm based on an S filter and a cutoff wavelength of 10 μm based on an L filter in accordance with ISO25178 and the level difference Sk of the center in μm, i.e., Sz×Sk, is greater than or equal to 0.25 and less than or equal to 0.
50.
4. The roughened copper foil according to claim 1 or 2, wherein: The interface expansion area ratio Sdr is 4.50% or more and 8.50% or less.
5. The roughened copper foil according to claim 1 or 2, wherein: The peak apex density Spd of the roughened surface measured in accordance with ISO 25178 under the conditions of a cutoff wavelength of 3.0 μm based on an S filter and a cutoff wavelength of 10 μm based on an L filter was 2.00×10 4 mm -2 Above and 3.00×10 4 mm -2 the following.
6. The roughened copper foil according to claim 1 or 2, wherein: The roughened surface has a surface texture aspect ratio Str of 0.2 or more and 0.5 or less, measured in accordance with ISO 25178 under the conditions of a cutoff wavelength of 0.55 μm using an S filter and a cutoff wavelength of 10 μm using an L filter.
7. The roughened copper foil according to claim 1 or 2, wherein: The maximum height Sz of the roughened surface measured in accordance with ISO 25178 under the conditions of a cutoff wavelength of 0.55 μm using an S filter and a cutoff wavelength of 10 μm using an L filter is 1.6 μm or less.
8. The roughened copper foil according to claim 1 or 2, wherein: The roughened surface is further provided with a rust-proofing layer and / or a silane coupling agent layer. 9 . A copper foil with a carrier, comprising: a carrier, a release layer provided on the carrier, and the roughened copper foil according to claim 1 provided on the release layer with the roughened surface facing the outside. 10 . A copper-clad laminate comprising the roughened copper foil according to claim 1 . 11 . A printed wiring board comprising the roughened copper foil according to claim 1 .
